Effects of combined exercise (aerobic + resistance) on the expression of miR-301a and some indicators of motor function in women with multiple sclerosis (MS) - saman yousefi saggezi; akbar azamian Jazi; Roohullah Hemmati; nahid jivad (Fasa University of Medical Sciences, 2019)
Background & Objective: Several evidence has indicated the effective role of exercise on Multiple sclerosis (MS) patients. An aberrant expression of some Micro-RNAs such as increasing miR-301a in MS, with an impact on inflammatory pathways leading to the creation of inflammation in these patients. The purpose of this study was to investigate the effect of a combined eight-week (aerobic and resistance) exercise on expression of miR -301a and some indicators of motor function in women with multiple sclerosis. Materials & Methods: A total of 22 women with MS, who were randomly divided into experimental and control groups, participated in this study. The experimental group performed 8 weeks (4 days per week) of combined training. Expression of miR -301a was measured before and after the training period using Real-Time PCR method. Pre- and post-intervention scores of tests (TUG), (6MWT), (10-MWT) and status scale (EDSS) were independent t-test recorded and analyzed. Results: The results of this study showed, the expression of miR -301a was significantly different between the two groups (P = 0.001). Tests TUG (P = 0.001), 6MWT (P = 0.002) and degree of disability EDSS (P = 0.015), were significantly different between the two groups. There was no significant difference between the 10MWT test between the two group (P = 0.678). Conclusion: The combined exercise for women with MS have been beneficial and improve motor function and reduce the expression of miR-301a. So, do it, plays an important role in reducing inflammation and prevent the progression of the disease Ms.